Comprehensive Organic Name Reactions and Reagents 2010
DOI: 10.1002/9780470638859.conrr369
|View full text |Cite
|
Sign up to set email alerts
|

Kolbe Electrolysis

Abstract: The Kolbe electrolysis involves the formation of symmetrical hydrocarbons through the coupling of radicals generated from carboxylic acid at an anode via electrolysis. The study shows that the free radicals have been used to initiate the polymerization for the preparation of low molecular weight polystyrene as well as polymers, but under certain conditions the generated radicals disproportionate and form carbocations. This reaction has been modified to occur in liquid ammonia. This reaction is useful for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Recently, Baran and co-workers demonstrated the use of electrochemistry to generate carbocations from nonactivated aliphatic carboxylic acids using Kolbe/Hofer-Moest chemistry. ,, These carbocations were captured by different alcohols to afford a range of hindered ethers, which are challenging to synthesize by conventional means. It was also reported that, in the presence of an excess of KF and 18-crown-6, the carbocations could be trapped to form the corresponding alkyl fluorides.…”
mentioning
confidence: 99%
“…Recently, Baran and co-workers demonstrated the use of electrochemistry to generate carbocations from nonactivated aliphatic carboxylic acids using Kolbe/Hofer-Moest chemistry. ,, These carbocations were captured by different alcohols to afford a range of hindered ethers, which are challenging to synthesize by conventional means. It was also reported that, in the presence of an excess of KF and 18-crown-6, the carbocations could be trapped to form the corresponding alkyl fluorides.…”
mentioning
confidence: 99%